DAYA HAMBAT GETAH TANAMAN JARAK TINTIR (Jatropha Multifida Linn) TERHADAP PROSES PENYEMBUHAN LUKA DI TINJAU DARI HASIL PEMERIKSAAN CLOTTING TIME - Siti Zaetun (Jurnal Kesehatan Prima, 2014)
Abstract: One of the herbs that can help in healing this wound is Jatropha (Jatropha multifida Linn). Jatropha sap is often used as an adjuvant in the treatment of injuries to the outside of the skin (Anonymous, 2010). The purpose of this study was to determine how different the results of blood clotting time with and without the addition of plant sap tintir Jatropha (Jatropha multifida Linn) "so that the sap of the plant determine the effectiveness of Jatropha tintir (Jatropha multifida Linn) is to help accelerate the process of wound healing. This research experiment is apparent that cross-sectional. Resulting data were analyzed with the Mann-Whitney Test Test. The results showed the mean clotting time results in venous blood samples without the addition of plant sap jatropha tintir (Jatropha multifida Linn) is 6.30 minutes, or approximately 6 minutes 18 seconds. The mean results of CT (clotting time) on venous blood samples with the addition of plant sap jatropha tintir (Jatropha multifida Linn) was 1.56 minutes, or approximately 1 minute 34 seconds. Test statistics indicate p = 0.000 <α (0.05) which means that there is a significant difference between the results of a CT (clotting time) Lee White method on blood samples without the addition of plant sap tintir jatropha (Jatropha multifida Linn) and with the addition of plant sap tintir  Jatropha (Jatropha multifida linn).